Perancangan Aplikasi Enkripsi Deskripsi Mengunakan Metode Caesar Chiper Berbasis Web - Mohammad Harun Alfirdaus; Muhlis Tahir; Nabilla Enno Dewanti; Riki Ardianto; Nela Nur Azurah; Nanang Firman Cahyono (Pusat Riset dan Inovasi Nasional, 2023)
Cryptography is a solution or method of information security that is good for maintaining the confidentiality and security of information, and can improve information or information security in an era of very rapid development of information technology. The rapid development of this technology, many new implications and problems arise in the delivery and communication of information, this is because everyone has easy access to the media and this affects the security of information and messages on the media. Therefore, to protect messages, we can use Caesar encryption, which is relatively easy to implement in PHP. How to apply message security in this study by designing web-based applications using the PHP and HTML programming languages. Message protection uses the Caesar encryption algorithm by changing every character of the original message into ciphertext. Characters in plain text are replaced with keys that are determined based on the number of alphabetical orders of plain text. In this way, unauthorized parties cannot read these private messages and users can interact with private messages more freely.